Hyperbolic discounting can be good for your health - Holger Strulik; Timo Trimborn (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2016)
It has been argued that hyperbolic discounting of future gains and losses leads to time-inconsistent behavior and thereby, in the context of health economics, not enough investment in health and too much indulgence of unhealthy consumption. Here, we challenge this view. We set up a life-cycle model of human aging and longevity in which individuals discount the future hyperbolically and make time-consistent decisions. This allows us to disentangle the role of discounting from the time consistency issue. We show that hyperbolically discounting individuals, under a reasonable normalization, invest more in their health than they would if they had a constant rate of time preference. Using a calibrated life-cycle model of human aging, we predict that the average U.S. American lives about 4 years longer with hyperbolic discounting than he would if he had applied a constant discount rate. The reason is that, under hyperbolic discounting, experiences in old age receive a relatively high weight in life time utility. In an extension we show that the introduction of health-dependent survival probability motivates an increasing discount rate for the elderly and, in the aggregate, a u-shaped pattern of the discount rate with respect to age.
Keywords: D03; D11; D91; I10; I12; 330; discount rates; present bias; health behavior; aging; longevity